PIPELINE STRENGTH ANALYSIS UNDER HYDRAULIC HAMMER (European Journal of Interdisciplinary Research and Development, 2026)
The process of pipe deformation under the influence of increased pressure during a hydraulic hammer caused by a flow interruption, the stress state of a pipe with an outer and inner diameter under load, and the differential equations of motion for elastic deformations were determined. A mathematical model of a pressure system resistant to hydraulic hammer and parameters for determining the minimum pipe wall thickness, taking into account the deformation of the pipe material, were developed.